Thompson and Thompson genetics in medicine - Nussbaum, Robert L
Originally published under the title: Genetics in medicine / James S. Thompson and Margaret W. Thompson; Includes bibliographical references and index; Introduction to the human genome -- The human genome: gene structure and function -- Human genetic diversity: mutation and polymorphism -- Principles of clinical cytogenetics and genome analysis -- The chromosomal and genomic basis of disease: disorders of the autosomes and sex chromosomes -- Patterns of single-gene inheritance -- Complex inheritance of common multifactorial disorders -- Genetic variation in populations -- Identifying the genetic basis for human disease -- The molecular basis of genetic disease : general principles and lessons from the hemoglobinopathies -- The molecular, biochemical, and cellular basis of genetic disease -- The treatment of genetic disease -- Developmental genetics and birth defects -- Cancer genetics and genomics -- Risk assessment and genetic counseling -- Prenatal diagnosis and screening -- Application of genomics to medicine and personalized health care -- Ethical and social issues in genetics and genomics